Barriers and facilitators to bicycle use in adults: a systematic review - Edina Camargo; Rogerio Fermino; Rodrigo Reis (Revista Brasileira de Atividade Física e Saúde)
The aim of this systematic review was to summarize the evidence on the barriers and facilitators to the use of bicycles in adults. Search terms were defined and was searched in the following databases: Lilacs, SciELO, PubMed, Web of Science and Science Direct. A total of seven studies met the inclusion criteria and showed that the main barriers and facilitators to the use of bicycles are related to the physical, social and natural environment characteristics and individual characteristics (cognitive, psychological and emotional aspects). Interventions in the area of public health should consider these features to increase the use of bicycles in adults.